PEMANFAATAN BIO-FUNGISIDASEBAGAI PENGHAMBAT ANTRAKNOSA UNTUK MENINGKATKAN MASA JUAL BUAH PEPAYA CALLINA - Emmy Darmawati; Florensius Labat Bionille (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2021)
Anthracnose is a disease that attacks papaya fruit while in the field and continues until the fruit is harvested and distributed to the market. Biofungiside made from citronella and green betel was expected to extend the selling papaya at inhibiting the growth of anthracnose. The study was aimed to determine the appropriate concentration of extracts of citronella leaves (Cymbopogon nardus L.) and green betel leaves (Piper betle L.) in inhibiting the growth of C. gloeosporioides as a cause of anthracnose. The extraction was done by boiling the leaves. The test methods used were in vitro and in vivo tests. In vitro tests were carried out to test the effectiveness of citronella leaf extract with concentrations of 5%, 10%, and 10%, 20% concentrations of green betel leaf extract in inhibiting the growth of C. gloeosporioides. The results of the in vitro test showed a significant difference (á = 0.5%) between treatments with the highest effectiveness value being 10% citronella extract with 47.22% growth inhibition of C. gloeosporioides and an average colony diameter of 3.150 cm after 15 days of incubation. The results of the in vivo test, showed significantly different results (á = 0.5%) between papaya fruit soaked with 10% citronella extract and controls, both in the incidence and spread of the disease. The spread of disease in treated papaya fruit was 13.72% while control papaya fruit reached 68.49% at 6 days of storage. Citronella extract with a concentration of 10% can extend the selling time of Calinna papaya (80% maturity index) 6 days longer than the control.